Opportunities and Challenges of Open Educational Resources for the Learning Communities - Munir Moosa Sadruddin (PJDOL, 2022)
This paper offers overarching insights into the benefits and drawbacks of Open Educational Resources (OER) for learning communities. A semi-systematic literature review (SSLR) is used as a research approach. Data is gathered from research articles, books, and other published work, and analyzed using thematic analysis. OER and Open Educational Practices (OEP) have the potential to support sustainable educational practices, but these have not yet reached their capacities to benefit wider learning communities. It is not yet known if the global academia is prepared towards embracing OEP due to limited pieces of evidence. OE policies have been successfully adopted by a few countries, but others have failed to accept open policies due to a lack of a supportive environment. M